Analysis of Student Learning Styles in Science Subjects at SMPN 40 Makassar - Arsyad, Arie Arma; Sari, Nur Indah (PT ARRUS Intelektual Indonesia, 2024)
Student learning style is one of the important information that a teacher needs to know before conducting learning activities, so that the teacher can determine the learning process that is suitable for the class. This descriptive quantitative research aims to analyze the characteristics of students' learning styles. The research subjects consisted of 23 students who were students of VIII.2, VII.4, and VIII.6 classes at SMP Negeri 40 Makassar. The learning style instrument is a multiple choice questionnaire, with a total of 50 questions, each question has five answer choices. The learning styles studied focus on Visual, Auditory, and Kinesthetic learning styles. The data were analyzed quantitatively by reducing data, presenting data, and making conclusions. The results of research on learning styles for classes VIII.2 and VIII.4 are auditory, while VIII.6 is a visual learning style and in general in class VIII at SMPN 40 Makassar are auditorial learning.